2002
DOI: 10.1016/s0890-6955(02)00040-8
|View full text |Cite
|
Sign up to set email alerts
|

A summary of methods applied to tool condition monitoring in drilling

Abstract: This paper presents a summary of the monitoring methods, signal analysis and diagnostic techniques for tool wear and failure monitoring in drilling that have been tested and reported in the literature. The paper covers only indirect monitoring methods such as force, vibration and current measurements, i.e. direct monitoring methods based on dimensional measurement etc. are not included. Signal analysis techniques cover all the methods that have been used with indirect measurements including e.g. statistical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(105 citation statements)
references
References 26 publications
0
105
0
Order By: Relevance
“…No lubricant was used and analysis of the results focussed on the drilling torque, power consumption of the spindle drive motor and the number of holes drilled before failure. Online monitoring of tool degradation is attractive economically and technically, and this experiment monitored the analogue current, which proportionally correlates to the drilling torque [11,12]. Since the cutting parameters (i.e., spindle speed, feed rate, drill geometry) are similar during each run of experiment, the variation in current signals can be attributed solely to the drill condition.…”
Section: Cutting Performancementioning
confidence: 99%
“…No lubricant was used and analysis of the results focussed on the drilling torque, power consumption of the spindle drive motor and the number of holes drilled before failure. Online monitoring of tool degradation is attractive economically and technically, and this experiment monitored the analogue current, which proportionally correlates to the drilling torque [11,12]. Since the cutting parameters (i.e., spindle speed, feed rate, drill geometry) are similar during each run of experiment, the variation in current signals can be attributed solely to the drill condition.…”
Section: Cutting Performancementioning
confidence: 99%
“…Root mean square (RMS) is the most common parameter used in statistical analysis [16]. Its value contains all the energy in the signal and therefore also all the noise and all elements that depend on the cutting process.…”
Section: Statistical Measurementmentioning
confidence: 99%
“…In the last three decades, various studies have been reported on the monitoring of drill wear which is focused on industrial applications (Jantunen 2002). However, drilling method in surgical operation theater is different as compared to industrial application.…”
Section: Introductionmentioning
confidence: 99%